Association of CLDN18 Protein Expression with Clinicopathological Features and Prognosis in Advanced Gastric and Gastroesophageal Junction Adenocarcinomas - Antonio Pellino (MDPI AG, 2021)
The tight junction protein claudin-18 (CLDN18), is often expressed in various cancer types including gastric (GC) and gastroesophageal adenocarcinomas (GECs). In the last years, the isoform CLDN18.2 emerged as a potential drug target in metastatic GCs, leading to the development of monoclonal antibodies against this protein. CLDN18.2 is the dominant isoform of CLDN18 in normal gastric and gastric cancer tissues. In this work, we evaluated the immunohistochemical (IHC) profile of CLDN18 and its correlation with clinical and histopathological features including p53, E-cadherin, MSH2, MSH6, MLH1, PMS2, HER2, EBER and PD-L1 combined positive score, in a large real-world and mono-institutional series of advanced GCs (n = 280) and GECs (n = 70). The association of IHC results with survival outcomes was also investigated. High membranous CLDN18 expression (2+ and 3+ intensity ≥75%) was found in 117/350 (33.4%) samples analyzed. CLDN18 expression correlated with age <70 (p = 0.0035), positive EBV status (p = 0.002), high stage (III, IV) at diagnosis (p = 0.003), peritoneal involvement (p < 0.001) and lower incidence of liver metastases (p = 0.013). CLDN18 did not correlate with overall survival. The predictive value of response of CLDN18 to targeted agents is under investigation in several clinical trials and further studies will be needed to select patients who could benefit from these therapies.